2007
DOI: 10.1590/s0103-05822007000400014
|View full text |Cite
|
Sign up to set email alerts
|

Colelitíase no paciente pediátrico portador de doença falciforme

Abstract: OBJETIVO: Considerando a alta freqüência da colelitíase no paciente pediátrico com doença falciforme e a controvérsia na literatura sobre a abordagem da condição, o presente texto objetiva revisar a literatura disponível. FONTE DE DADOS: Revisão dos estudos sobre colelitíase no paciente falciforme, publicados no período entre 1980 e 2007, em língua inglesa e portuguesa, envolvendo pacientes na faixa etária de zero a 18 anos e utilizando os bancos de dados Medline e Lilacs. SÍNTESE DOS DADOS: A colelitíase é a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
2
0
4
Order By: Relevance
“…SCD patients are prone to developing gallstones. (2,7,23) In a comprehensive review of the literature on cholelithiasis in SCD, (24) four of seven authors indicated cholecystectomy in patients with asymptomatic cholelithiasis to prevent possible complications such as choledocholithiasis,…”
Section: Discussionmentioning
confidence: 99%
“…SCD patients are prone to developing gallstones. (2,7,23) In a comprehensive review of the literature on cholelithiasis in SCD, (24) four of seven authors indicated cholecystectomy in patients with asymptomatic cholelithiasis to prevent possible complications such as choledocholithiasis,…”
Section: Discussionmentioning
confidence: 99%
“…In young adult males, 5 to 10% suffer from priapism and 45% present some degree of impotence later in life. [6][7][8][9][10] Most prevalent clinical complications in patients with sickle cell disease from a medium-sized town in Minas Gerais, Brazil ment, the pilot study data were not considered in this analysis. Out of the 83 patients elected for the interview, four were excluded because they moved away from Divinópolis, 14 were considered lost, eight were not found, and four had died.…”
Section: Methodsmentioning
confidence: 99%
“…Assim, uma parcela significativa da população com AF é propensa à colelitíase, principalmente, com o avançar da idade. Além disso, a obstrução do ducto biliar comum também foi percebida como uma complicação muito comum em crianças e adultos jovens que apresentam doença falciforme e doença do trato biliar mais do que na população geral (Froed, et al, 2012;Al Talhi et al, 2017;Gumiero et al, 2007).…”
Section: Introductionunclassified